Agricultural Modernization: Process and Influences among the Farmers in Cilacap, 1979-1999 - Firdausi, Tsuroya; Rochwulaningsih, Yety; Rinardi, Haryono (Diponegoro University, 2023)
This study discusses changes in the use of technology in agriculture in Cilacap during the 1979-1999 period. This study uses a socio-economic approach to examine changes in agricultural cultivation technology in Cilacap. The study also analyzes the relationship between changes in agricultural cultivation technology in Cilacap and the development of agricultural production in Cilacap in the same period. This study uses critical historical research methods, which include four steps. First, heuristics, namely collecting relevant historical data or sources. Second is source criticism, studying the authenticity and credibility of the sources obtained, namely in terms of the physical and content of the sources. Third, interpretation is scrutinizing for interrelationships of meanings related to historical facts. Fourth is historiography or writing, namely the delivery of synthesis in historical works. Agricultural modernization was a government policy to increase agricultural production, especially rice as a staple food in the Cilacap Regency area. The Mass Guidance Program, or BIMAS, marks the modernization of agriculture in the Cilacap district by providing production facilities in the form of fertilizers, seeds and pesticides to farmers. Through the Community Guidance Program, farmers knew how to grow crops properly. They started using superior seeds, chemical fertilizers, anti-pest insecticides, integrated cultivation systems, and so forth. Farmers were able to increase their agricultural production through a series of changes in agricultural cultivation, especially rice. As a result, Indonesia experienced food self-sufficiency during the early 1980s.